Co(mplex)city – User as urban sensor and accessible mobility in the Mobiquity project - Nicola Valentino Canessa; Chiara Centanaro (Agathón)
The new media technology tools and co-production processes used in the ongoing POR FESR Mobiquity – Shared Solutions for Safe and Inclusive Mobility project aim to increase the complexity of reading the city, identifying those who live the territory the interlocutor to build shared projects and improve the accessibility of urban services. The project investigates the theme of public transport accessible to all as an element of redesigning the city; through the application of transdisciplinary processes in the multicity, the project investigation is constructed through the relationship of quantitative and qualitative, objective and subjective data, in a decision-making ecosystem involving Administrations, the University, public transport companies and citizens, for the transition to the Co(mplex)city.